2016
DOI: 10.4322/2357-9730.68880
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofitoses: agentes etiológicos, formas clínicas, terapêutica e novas perspectivas de tratamento

Abstract: As dermatofitoses têm ocorrência mundial, sendo mais prevalentes em países de clima tropical e subtropical. Dados epidemiológicos indicam que essas micoses estão entre as infecções fúngicas de maior ocorrência. O quadro clínico mais comum de dermatofitose inclui despigmentação, placas anulares, prurido e perda de cabelo, com lesões tipicamente conhecidas como tineas, ocasionadas por fungos filamentosos dermatofíticos de três gêneros anamórficos: Microsporum, Trichophyton e Epidermophyton. O tratamento das derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 75 publications
0
11
0
1
Order By: Relevance
“…17-21 Comparing these data with studies conducted in Spain and the United States, we can observe the same etiology for T. rubrum complex and T. mentagrophytes complex. 18,19 It is observed that these dermatophytes are the most common causative agents for nail lesions and are the typical agents in regions with subtropical climate and the southern region of Brazil. 21-23…”
Section: Discussionmentioning
confidence: 99%
“…17-21 Comparing these data with studies conducted in Spain and the United States, we can observe the same etiology for T. rubrum complex and T. mentagrophytes complex. 18,19 It is observed that these dermatophytes are the most common causative agents for nail lesions and are the typical agents in regions with subtropical climate and the southern region of Brazil. 21-23…”
Section: Discussionmentioning
confidence: 99%
“…The condition is caused mainly by T. rubrum , T. mentagrophytes var. interdigitale and Epidermophyton floccosum , and men are more affected than women [ 19 ]. The main causative agent of tinea corporis is T. rubrum , which is responsible for 80 to 90% of infections.…”
Section: Epidemiology Of Infections Caused By Dermatophytesmentioning
confidence: 99%
“…Noteworthy, the drug was not detected in the receptor compartment solution. Compound retained in these outermost layers of the skin is extremely advantageous for the treatment of dermatomycoses, such as dermatophytosis and superficial/cutaneous candidiasis, which have the epidermis as the main site of infection and which are recognised as being difficult to treat . This result brings a more real approximation of its potential therapeutic use.…”
Section: Resultsmentioning
confidence: 99%
“…Dermatophytes are keratinophilic fungi, comprising species of three anamorphic genera— Microsporum , Trichophyton and Epidermophyton . Trichophyton rubrum , Trichophyton mentagrophytes and more recently Microsporum canis have been identified as a biofilm‐forming species, which worsens the therapeutic response .…”
Section: Introductionmentioning
confidence: 99%